Racjonalność zagrana. O pojęciu racjonalności w dramaturgicznej koncepcji Ervinga Goffmana - Urban, Olga (Człowiek i Społeczeństwo, 2017)
This study looks at the sources of the Erving Goffmann’s dramaturgical analysis – humanistic sociology, symbolic interactionism and functionalism. Taking into account the impact of these traditions on Goffman’s analysis, the problem of human rationality is highlighted. The category of management impressions corresponding to the Max Weber’s notion of rationality, which characteristic feature is focusing on achieving the objective by identifying and using optimal means of its realisation. This rationality was called “played” as the rational is the one, who knows how to play as himself effectively, credibly and acceptably to others. Olga Urban, Racjonalność zagrana. O pojęciu racjonalności w dramaturgicznej koncepcji Ervinga Goffmana [Played rationality. About the notion of rationality in the dramaturgical analysis by Erving Goffmann], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 203-216, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.